2019
DOI: 10.1016/j.bandl.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive basis of repetition deficits in primary progressive aphasia

Abstract: Previous studies indicate that repetition is affected in primary progressive aphasia (PPA), particularly in the logopenic variant, due to limited auditory-verbal short-term memory (avSTM). We tested repetition of phrases varied by length (short, long) and meaning (meaningful, non-meaningful) in 58 participants (22 logopenic, 19 nonfluent, and 17 semantic variants) and 21 healthy controls using a modified Bayles repetition test. We evaluated the relation between cortical thickness and repetition performance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 65 publications
7
60
2
1
Order By: Relevance
“…A sizeable number of studies administered and reported the total score of the widely used Repetition subtest of the Western Aphasia Battery, which combines repetition of words, phrases, and sentences. Lukic et al (2019) and others have noted that the final six sentences are the most difficult items and are sensitive to the repetition difficulties characteristics of lvPPA. However, since studies typically combine measures of varying complexity, future PPA studies that separate repetition scores by difficulty level and meaning will be important for improving the clinical utility of repetition measures in the differential diagnosis of PPA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A sizeable number of studies administered and reported the total score of the widely used Repetition subtest of the Western Aphasia Battery, which combines repetition of words, phrases, and sentences. Lukic et al (2019) and others have noted that the final six sentences are the most difficult items and are sensitive to the repetition difficulties characteristics of lvPPA. However, since studies typically combine measures of varying complexity, future PPA studies that separate repetition scores by difficulty level and meaning will be important for improving the clinical utility of repetition measures in the differential diagnosis of PPA.…”
Section: Discussionmentioning
confidence: 95%
“…lvPPA patients show poorer performance on repetition tasks across different length conditions, with greater deficits observed for repetition of long phrases and non-meaningful phrases (Lukic et al, 2019). Based on this work, we generated an effect size for repetition deficits in lvPPA that excluded performance on simple and mixed repetition tasks.…”
Section: Discussionmentioning
confidence: 99%
“…1). Naming difficulties in lvPPA correlate with left middle temporal gyrus atrophy [66], whereas repetition deficits correlate with temporoparietal junction damage [67]. White matter damage in lvPPA is less severe than in nfvPPA and involves left dorsal parietal white matter tracts that connect frontal and posterior temporal regions [22] (Fig.…”
Section: Logopenic Variant Primary Progressive Aphasiamentioning
confidence: 99%
“…Previous studies investigating repetition in PPA support the involvement of this temporoparietal phonological buffer in verbal repetition tasks (Amici et al, 2007;Rogalski et al, 2011;Leyton et al, 2012;Lukic et al, 2019). The current study seeks to extend this work to test for the involvement of an additional phonological content buffer in left pIFS in sentence repetition and digit span working memory tasks, as predicted by GODIVA model.…”
Section: Introductionmentioning
confidence: 66%
“…For example, the characteristic anterior temporal atrophy in svPPA is associated with single-word comprehension abilities, while distinctive left inferior frontal atrophy in nfvPPA correlates with measures of syntactic processing (Amici et al, 2007;Sapolsky et al, 2010;Rogalski et al, 2011). LvPPA is associated with cortical thinning in the temporoparietal junction, with atrophy here also correlated with sentence repetition abilities (Amici et al, 2007;Rogalski et al, 2011;Lukic et al, 2019).…”
Section: Introductionmentioning
confidence: 89%